THE IMPACT OF THE COVID-19 PANDEMIC ON THE STABILITY OF RURAL BANK IN BULELENG REGENCY - Yudiaatmaja, Fridayana; ., Trianasari (Buletin Studi Ekonomi; VOLUME.29.NO.01.TAHUN.2024, 2024)
The purpose of this study was to determine the significance of the impact of the Covid-19 Pandemic on the Stability of Rural Bank in Buleleng Regency. The data collection technique used in this research is documentation technique. The documentation carried out is by collecting secondary data in the form of rural bank financial reports (balance sheet and profit and loss) obtained from the Financial Services Authority (OJK) website. The data were analyzed using Android based t-test application namely Uji Beda to distinguish the stability of rural banks before and after the Covid-19 pandemic. The research results show that the Covid-19 pandemic has had a negative impact on the stability of several individual rural banks, but the pandemic has not had a negative impact on the stability of rural banks in Buleleng Regency as a whole. The overall stability of rural banks in Buleleng Regency can be well maintained because it turns out that rural banks are still able to increase their capital.